Community of anurans in an ecotonal area in northeastern Brazil - Benício, Ronildo Alves; Silva, Guilherme Ramos da; Fonseca, Mariluce Gonçalves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
We present data on a community of anurans and their distribution patterns in an ecotonal area in northeastern Brazil. Collections were made biannually from July 2007 to July 2012 using visual and auditory active search in permanent and temporary water bodies. We recorded 27 species belonging to 13 genera and five families. Hylidae was the family with the highest number of species (44%, n = 12 spp.), followed by the family Leptodactylidae (37%, n = 10). Although 40% of the species are widely distributed geographical, three species are restricted exclusively in areas of Cerrado (Rhinella mirandaribeiroi, Dendropsophus rubicundulus and Leptodactylus pustulatus), one exclusively in areas of Caatinga (Rhinella jimi) and one occurs in the Amazon and Cerrado biomes (Sphaenorhynchus lacteus). Regarding habitat use, most species (52%, n = 14) occurred in more than one environment, however, seven species (26%) were restricted to areas of Semideciduous Seasonal Forest. Understanding how many species, which ones, and how they are distributed in transitional environments is extremely important for conservationists, because these environments support a high biological diversity.